Gender Inequalities in Education - Buchmann, Claudia; DiPrete, Thomas A.; McDaniel, Anne (Annual Review of Sociology, 2008)
The terrain of gender inequalities in education has seen much change in recent decades. This article reviews the empirical research and theoretical perspectives on gender inequalities in educational performance and attainment from early childhood to young adulthood. Much of the literature on children and adolescents attends to performance differences between girls and boys. Of course, achievement in elementary and secondary school is linked to the level of education one ultimately attains including high school completion, enrollment in postsecondary education, college completion, and graduate and professional school experiences. We recommend three directions for future research: (a) interdisciplinary efforts to understand gender differences in cognitive development and noncognitive abilities in early childhood, (b) research on the structure and practices of schooling, and (c) analyses of how gender differences might amplify other kinds of inequalities, such as racial, ethnic, class, or nativity inequalities.